2020
DOI: 10.1186/s13075-020-2097-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of toll-like receptor (TLR) 4 inhibitor TAK-242 as a new potential anti-rheumatoid arthritis drug

Abstract: Background: Proper blocking of toll-like receptor (TLR) activation during disease progression has been reported to have inhibitory effect on the pathogenesis of rheumatoid arthritis (RA). We tested whether the TLR4 inhibitor TAK-242 had potential as a remedy for rheumatoid arthritis. Methods: The therapeutic effect of TAK-242 was tested in vitro using the human rheumatoid fibroblast-like synoviocyte (FLS) line MH7A or primary human FLS and in an adjuvant-induced arthritis (AIA) rat model. Results: TAK-242 dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 33 publications
(41 reference statements)
2
60
0
Order By: Relevance
“…In addition, our study identified that overexpression of OIP5‐AS1 decreased TLR3 activity and NF‐κB p65 phosphorylation in RA rat synovial tissues. The TLRs–NF‐κB signalling pathways have been recognized to participate in RA pathogenesis, among which the roles of TLR4 have been largely investigated (Kim, Bang, Son, Baek, & Kim, 2018; Samarpita, Kim, Rasool, & Kim, 2020). Likewise, TLR3 up‐regulation and NF‐κB activation have been evidenced in synovial fibroblasts in a mouse model with RA (Yu, Xie, Jiang, Sun, & Huang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study identified that overexpression of OIP5‐AS1 decreased TLR3 activity and NF‐κB p65 phosphorylation in RA rat synovial tissues. The TLRs–NF‐κB signalling pathways have been recognized to participate in RA pathogenesis, among which the roles of TLR4 have been largely investigated (Kim, Bang, Son, Baek, & Kim, 2018; Samarpita, Kim, Rasool, & Kim, 2020). Likewise, TLR3 up‐regulation and NF‐κB activation have been evidenced in synovial fibroblasts in a mouse model with RA (Yu, Xie, Jiang, Sun, & Huang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Biological disease-modifying antirheumatic drugs, such as anti-TNF-α antibodies, have shown considerable efficacy in clinical practice, but many patients continue to have active disease [ 32 ]. TLR-4 inhibitor therapy for RA is considered one further promising candidate [ 33 ], and several TLR-4 inhibitors have demonstrated some therapeutic effect in vitro and in vivo [ 34 ]. In fact, an anti-TLR-4 monoclonal antibody has now advanced to a phase II clinical trial [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, multiple omics analysis mapped to significant pathways allows for the simultaneous detection of target genes and human proteins for their potential in specific diseases. For instance, drug candidates and human protein targets have been identified for several diseases such as dengue haemorrhagic fever [27], head and neck squamous cell carcinoma [28] and rheumatoid arthritis [29] amongst many others, using this approach. However, there are also downsides to this approach.…”
Section: Pathway Mappingmentioning
confidence: 99%